Revitalisasi Kinerja Badan Pengawasan Desa (BPD) Dalam Pengawasan Pemerintahan Desa Lingkis - Yamin, Alex Muhammad; Minako, Muchlis (Indonesian Journal Publisher, 2023)
This research is to find out the duties and performance of the BPD towards the Lingkis village government. With this research, it is hoped that the community can know clearly, know what the village supervisory agency is doing in the village scope and what it can do for the village government. research methoda This research is entitled the role of BPD in the government of Lingkis village, Jejawi sub-district, Ogan Komering Ilir district. In this study using in-depth qualitative research methods, following the process carried out by the research itself, may not be represented or ordered by others to collect data. This research uses descriptive qualitative. Through a descriptive approach, in this study the researcher will make a description, description , or painting systematically, factually, accurately regarding the facts and the relationships between the phenomena found. This, of course, was obtained from the results of data collection by the researcher and some of the findings in the field that were taken by the researcher, thus these matters influence decision making and must be considered carefully and thoroughly so that there are no errors on the part of the researcher. The conclusion is based on the data obtained in the field that there was an error in the data and a lack of communication between the BPD and the Lingkis village government and then from the results of a meeting between residents and the government and the meeting was facilitated at the PMD office in OKI district with the meeting discussing and with satisfactory results for lingkis villagers.